Economic evaluation of mineral supplemented steers kept on fertilized guineagrass - Costa, Fernando Paim; Sousa, Júlio Cesar de; Gomes, Ronaldo Frederico Correa; Silva, José Marques da; Euclides, Valéria Pacheco Batista (Pesquisa Agropecuaria Brasileira, 2014)
Three alternatives to mineral supplementation (common salt; common salt plus phosphorus; and common salt plus phosphorus and micronutrients) were economically evaluated when fed to nelore steers weighing initially 170 kg. These animals were kept on fertilized guineagrass up to slaughter, in the state of Mato Grosso do Sul, Brazil. The most economically interesting alternative was using common salt. If we analyse the dry season alone, this alternative isn’t economical since the animals showed no weight gain in response to this treatment.
Keywords: supplementation economics; animal nutrition